Modulatory Role of Vitamins A and E on Memory and Motor Functions of Cyanide Induced Neurotoxicity in Adult Swiss Mice (Nigerian Journal of Physiological Sciences, 2021)
Summary: Cyanide is a potent neurotoxic substance that can initiate series of intracellular reactions leading to oxidative stress. To evaluate effect of sublethal administration of potassium cyanide (KCN) on sensorimotor functions and long term visuo-spatial learning and memory in adult Swiss mice and possible ameliorative role of vitamins A and E. These vitamins A and E (dietary) are antioxidants that have scavenging properties against free radicals and reactive oxygen species as a result of oxidative stress induced by cyanide. Thirty-five mice weighing between 18-22 g were used for the study. The animals were randomly divided into five groups (n = 7) and exposed to sublethal concentration of potassium cyanide (10% LD50; 1.5 mg/kg). KCN was administered orally while vitamin A (25 mg/kg) and vitamin E (50 mg/kg) were administered intra-peritoneal (IP) once daily for 28 days. Potassium cyanide (KCN) was first administered and after 10 minutes intervals, followed by vitamin A and then E after 5 minutes, vitamin E were administered across the different treatment groups. Mice were examined for signs of toxicity. Vitamins pre-treatment ameliorated toxic signs. In the dynamics of wire grid, coat hanger and stationary beam test, the latency to fall in weeks 2 and 4 were statistically significant. In acquisition and retention, using elevated plus maze (EPM), KCN treated group recorded high transfer latencies in seconds (50.40±1.72 secs) and (57.60±0.93 secs) as compared to group IV (29.40±0.68 secs; 5.60±0.60 secs). Cyanide is a neurotoxin that affects motor functions with progressive decline in motor strength and coordination. KCN affects acquisition and retention memory while pre-treatment with antioxidant vitamins A and E ameliorated these deficits.